2016
DOI: 10.1080/00102202.2016.1197211
|View full text |Cite
|
Sign up to set email alerts
|

Velocity and Reactive Scalar Dissipation Spectra in Turbulent Premixed Flames

Abstract: Dissipation spectra of velocity and reactive scalars-temperature and fuel mass fraction-in turbulent premixed flames are studied using direct numerical simulation data of a temporally evolving lean hydrogen-air premixed planar jet (PTJ) flame and a statistically stationary planar lean methane-air (SP) flame. The equivalence ratio in both cases was 0.7, the pressure 1 atm while the unburned temperature was 700 K for the hydrogen-air PTJ case and 300 K for methane-air SP case, resulting in data sets with a densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…It has recently been reported that the heat release due to combustion modifies the spectra of turbulent kinetic energy (Kolla et al 2014) and its dissipation rate (Kolla et al 2016) in turbulent premixed flames in comparison to the corresponding results obtained for turbulent non-reacting flows. The two-point velocity correlations for the velocity field in turbulent premixed flames need to account for density differences between two points in question due to thermal expansion effects.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has recently been reported that the heat release due to combustion modifies the spectra of turbulent kinetic energy (Kolla et al 2014) and its dissipation rate (Kolla et al 2016) in turbulent premixed flames in comparison to the corresponding results obtained for turbulent non-reacting flows. The two-point velocity correlations for the velocity field in turbulent premixed flames need to account for density differences between two points in question due to thermal expansion effects.…”
Section: Introductionmentioning
confidence: 92%
“…The two-point velocity correlations for the velocity field in turbulent premixed flames need to account for density differences between two points in question due to thermal expansion effects. This type of spectral analysis has the potential to provide insights into the scales where the correlation between pressure and dilatation remains important, which, in turn, affect the spectral energy transfer from lower to higher wavenumbers (Kolla et al 2014(Kolla et al , 2016. The predominantly positive dilatation rate due to thermal expansion in premixed turbulent flames also influences turbulent kinetic energy transport through the correlation between pressure and dilatation rate (Zhang and Rutland 1995;Nishiki et al 2002;Chakraborty and Cant 2009c;Chakraborty et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…The SP dataset is from the simulation of a three-dimensional statistically steady planar turbulent premixed flame of methane-air combustion. The simulation considers reduced chemical kinetics of 6 species, which results in a total of 11 simulation variables [14]. Unlike the HCCI and TJLR datasets, the SP dataset represents a statistically steady, rather than a temporally evolving, turbulent flame.…”
Section: A Data Descriptionmentioning
confidence: 99%
“…Also, velocity and scalar dissipation spectra deduced using DNS data of premixed flames lend support for this view. 43 . Hence, we shall use Eq.…”
Section: Scalar and Its Dissipation Spectramentioning
confidence: 99%